Lessons from the British and French new towns : paradise lost? - Fée, David; Colenutt, Bob; Coady Schäbitz, Sabine (Emerald Publishing Limited, 2020)
Lessons from the British and French New Towns: Paradise Lost? explores the evolution of the New Towns in both France and the UK from several perspectives including public policy, sociology, geography and heritage. UK and French New Towns have many similarities in terms of the role of the national state in tackling urgent problems of housing and urban growth and in promoting innovative design and architecture. These innovative planned settlements have left a contested and complex legacy, but are once again on the political and urbanisation agenda in Europe, where a push for growth of housing and the desire for sustainability are the new drivers of urban planning and design. After years of the private development market being seen as the principal instrument of urban growth and planning, it is time to assess the urban legacy and the heritage of the UK and French New Towns. This book contrasts their evolution on both sides of the Channel and shows what can be learned about post war state planning and the future planning of new settlements.